Lupinus luteus, a new host of Phytophthora cinnamomi in Spanish oak-rangeland ecosystems (European Journal of Plant Pathology, 2010)
Phytophthora cinnamomi is an aggressive pathogen on Lupinus luteus (yellow lupin), causing root rot, wilting and death of this crop, common in oak-rangeland ecosystems ('dehesas') in south-western Spain. The oomycete, the main cause of Quercus decline in the region, was isolated from roots of wilted lupins in the field. Artificial inoculations on four cultivars of L. luteus reproduced the symptoms of the disease, both in pre- and post-emergence stages, recovering the pathogen from necrotic roots. These results suggest the potential of yellow lupin as inoculum reservoir for the infection of Quercus roots. This is the first report of P. cinnamomi as root pathogen of L. luteus.